Women’s Development Bank
Documentary on the Womens Development Bank (WDB) and the pro-poor microfinance sector for women living in rural areas in South Africa. It features an interview with activist and social worker Zanele Mbeki, First Lady of South Africa from 1998 to 2008 and founder of the WDB.